Analyzing Deixis of English Speech by Kim Namjoon (BTS) at the United Nations - St. Ika Susanti; Iin Widya Lestari; Khoirul Wafa (GLENS: Global English Insights Journal, 2023)
Humans, as social beings, naturally interact to fulfill various life needs. This study aimed to analyze different deixis types in Kim Namjoon's speech and understand their meanings. The research employed Stephen C. Levinson's Theory and utilized a descriptive qualitative method with a content analysis approach. The findings revealed five deixis categories in Kim Namjoon's speech: personal, spatial, temporal, discourse, and social. These were distributed as follows: 129 (65.8%) personal deixis, 15 (7.7%) spatial deixis, 10 (5.1%) temporal deixis, 31 (15.8%) discourse deixis, and 11 (5.6%) social deixis. In total, 196 deixis instances were identified in Kim Namjoon's speech. His speech, titled "Speak Yourself," aimed to inspire young people to embrace self-love, discover their inner voices, and confidently express themselves to the world. The significance of this research lies in enhancing our understanding of deixis and its role as a linguistic resource, particularly in terms of usage and significance within utterances.